2002
DOI: 10.1007/s10123-002-0064-1
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal microbiota in healthy pregnant women and prenatal screening of group B streptococci (GBS)

Abstract: The microbiota of the lower female genital tract was evaluated from vaginal swabs obtained from 623 healthy pregnant women at gestation periods of 35-40 weeks. Isolated and identified microorganisms were expressed as percentages of total samples. As expected, lactobacilli made up the dominant vaginal microbiota (70%). Enterobacteriaceae, mainly Escherichia coli, Klebsiella spp. and Proteus, were present in 38% of the samples, which might reflect the possible contamination of vaginal tract with rectal microorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…[18,21,28] S. aureus, Candida albicans, C. trachomatis, and Treponema pallidum topped the list of pathogens. Similar reports exist in Spain [29] and Argentina. [16] The World's AIDS day urged all to have access to sexual health services and interventions.…”
Section: Discussionsupporting
confidence: 78%
“…[18,21,28] S. aureus, Candida albicans, C. trachomatis, and Treponema pallidum topped the list of pathogens. Similar reports exist in Spain [29] and Argentina. [16] The World's AIDS day urged all to have access to sexual health services and interventions.…”
Section: Discussionsupporting
confidence: 78%
“…This study provides the first evidence of interkingdom interactions between GBS and C. albicans. Given the reported co-isolation of these two species (33)(34)(35), candidal/GBS interactions may serve as an important mechanism to promote co-colonization of the GU tract. BspA-expressing L. lactis cells were shown to interact with C. albicans, binding preferentially to hyphal filaments.…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans co-exists with GBS in the lower female GU tract, and several studies have observed recurrent co-isolation of GBS with C. albicans (33)(34)(35). To confirm the capacity for GBS to interact with C. albicans, FITC-labeled GBS NEM316 cells were incubated in suspension with hyphaforming cells of C. albicans SC5314 labeled with calcofluor white, and aggregates were visualized by fluorescence microscopy.…”
Section: Distribution Of Agi/ii Polypeptides In Gbs-mentioning
confidence: 99%
“…constituting around 70% of the microbial population (1,2). They appear to protect the urogenital tract from pathogen invasion and prevent urogenital and sexually transmitted diseases (3,4).…”
mentioning
confidence: 99%